2016
DOI: 10.1155/2016/1346390
|View full text |Cite
|
Sign up to set email alerts
|

Epobis is a Nonerythropoietic and Neuroprotective Agonist of the Erythropoietin Receptor with Anti-Inflammatory and Memory Enhancing Effects

Abstract: The cytokine erythropoietin (EPO) stimulates proliferation and differentiation of erythroid progenitor cells. Moreover, EPO has neuroprotective, anti-inflammatory, and antioxidative effects, but the use of EPO as a neuroprotective agent is hampered by its erythropoietic activity. We have recently designed the synthetic, dendrimeric peptide, Epobis, derived from the sequence of human EPO. This peptide binds the EPO receptor and promotes neuritogenesis and neuronal cell survival. Here we demonstrate that Epobis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 53 publications
(83 reference statements)
0
17
0
1
Order By: Relevance
“…There are emerging evidences for the neuroprotection effect of EPO both in vivo and in vitro [21,38,39]. The positive roles that EPO may play in APAC under higher dose, such as anti-apoptotic [12,13], anti-oxidant [14], and antiin ammatory [15,16] make it an ideal treatment in APAC. However, its role in angiogenesis, causing neovascularization is a dreaded occurrence in the eye [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are emerging evidences for the neuroprotection effect of EPO both in vivo and in vitro [21,38,39]. The positive roles that EPO may play in APAC under higher dose, such as anti-apoptotic [12,13], anti-oxidant [14], and antiin ammatory [15,16] make it an ideal treatment in APAC. However, its role in angiogenesis, causing neovascularization is a dreaded occurrence in the eye [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been no research describing the changes of EPO and PDGF levels in APAC eyes. Recent studies have shown that both EPO and PDGF have neuroprotective functions such as anti-apoptotic [12,13], anti-oxidant [14] and anti-in ammatory properties [15,16]. Thus, the uctuations of their levels in aqueous humor may correlate with prognosis of trabeculectomy in APAC eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Several protective effects of EPO against ischemia were demonstrated in cell cultures and animal models, including anti-apoptotic, antioxidant, and neuroprotective effects (20,21). There are studies indicating that EPO decreases the damage caused by ischemia/reperfusion in kidneys (22) and colon (23).…”
Section: Discussionmentioning
confidence: 99%
“…При системном введении Epobis крысам на модели аутоиммунного энцефалита пептид задерживает наступление признаков поражения. Также отмечен долговременный эффект пептида на рабочую и социальную память крыс [63].…”
Section: пептидные производные эритропоэтина обладающие тканезащитныunclassified